Social history of the deccan 1300-1761 - Eaton, Richard M. (New Delhi Cambridge University, 2021)
Richard Eaton has again magisterially pushed back the boundaries of history writing on pre-colonial South Asia. A Social History of the Deccan, 1300-1761, inspired in part by Vermeer's 'finely crafted portraits with their distinctive play of light.
Keywords: History; India--Deccan; Social conditions